2019
DOI: 10.1007/s11548-019-02030-z
|View full text |Cite
|
Sign up to set email alerts
|

Moving object tracking in clinical scenarios: application to cardiac surgery and cerebral aneurysm clipping

Abstract: Background and objectivesSurgical procedures such as laparoscopic and robotic surgeries are popular since they are invasive in nature and use miniaturized surgical instruments for small incisions. Tracking of the instruments (graspers, needle drivers) and field of view from the stereoscopic camera during surgery could further help the surgeons to remain focussed and reduce the probability of committing any mistakes. Tracking is usually preferred in computerized video surveillance, traffic monitoring, military … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Loss of mural cells and further inflammation and vessel wall degeneration ultimately lead to cerebral arteries rupture 81 . Rupture of cerebral aneurysms can cause subarachnoid haemorrhage, intracerebral hematoma and other complications leading to high mortality rate 82 . In our previous study, we found that prophylactic administration of borneol could reduce the damage caused by subarachnoid haemorrhage in the brainstem.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Loss of mural cells and further inflammation and vessel wall degeneration ultimately lead to cerebral arteries rupture 81 . Rupture of cerebral aneurysms can cause subarachnoid haemorrhage, intracerebral hematoma and other complications leading to high mortality rate 82 . In our previous study, we found that prophylactic administration of borneol could reduce the damage caused by subarachnoid haemorrhage in the brainstem.…”
Section: Discussionmentioning
confidence: 98%
“…81 Rupture of cerebral aneurysms can cause subarachnoid haemorrhage, intracerebral hematoma and other complications leading to high mortality rate. 82 In our previous study, we found that prophylactic administration of borneol could reduce the damage caused by subarachnoid haemorrhage in the brainstem. This study also shows that borneol can impact the BBB, regulate inflammatory response and promote angiogenesis, alleviating the damage of local vascular wall and preventing the formation of cerebral aneurysms.…”
Section: Downregulation Of the Inflammatory Response And Oxidative St...mentioning
confidence: 93%
“…Segmentation was even considered as tracking the cardiac dynamics. Hybrid algorithms (Tran, Tran, Ninh, Bui, & Pham, 2020) using discrete wavelet transform (Dakua et al, 2019), level set method, and k-means clustering also proved its good performance in left ventricle segmentation (Nageswararao & Srinivasan, 2014).…”
Section: Related Workmentioning
confidence: 90%
“…There are motion tracking systems in use for laparoscopic surgery, [16][17][18] but none are available for open surgery. A reason may be that routine video recording is not an absolute must in open surgery.…”
Section: Discussionmentioning
confidence: 99%